(untitled) (International relations and international law Journal, 2024)
This research focuses on the analysis of return migration from the Russian Federation to the Kyrgyz Republic, with a particular emphasis on the phenomenon of «digital nomads» in the last decade, especially in the post-COVID-19 period. The introduction underscores the relevance of migration issues and their impact on societal processes. The study aims to identify the main directions and ideas of return migration, shed light on the characteristics of «digital nomads» and explore their influence on socio-cultural aspects in Kyrgyzstan. Digital nomads are people who travel all over the world and work remotely. The research methodology includes the analysis of statistical data, comparative method, retrospective method, and descriptive method. The obtained results and analysis enable the identification of key factors in return migration and an assessment of their impact on societal processes in the country. The scientific and practical significance of the study is manifested in a deeper understanding of the dynamics of migration processes and their impact on the social sphere of Kyrgyzstan. The research contributes to the field of knowledge by revealing new aspects of return migration and its influence on the emergence of «digital nomads». Practical value lies in the opportunity to develop more effective policies and programs aimed at the integration of returning migrants and support for their adaptation in their home country. Key words: «digital nomads», migration, Kyrgyz Republic, Russia